علمائے فرنگی محل کی خدمات ِحدیث: ایک مطالعہ: A Study of the Contributions of the Scholars of Farangī Maḥal in Ḥadīth (Al-Qamar, 2021)
The Ulema-e-Farangī Maḥal class has been performing religious services for the last one thousand years. The lineage of this class goes back to the host Prophet Abū Ayyub Ansari. The reason for this is the fame of the premises of Farangī Palace that was known as Farangī. After the martyrdom of Maulana Quṭbuddīn Shaheed Sahalī in Sahalī, his entire family moved to Farangī Maḥal in a neighborhood of Lucknow where Mullah Nizāmuddīn established a madrassa and organized a teaching, which later became known as Dars-e-Nizāmī. The services of Ulema-e- Farangī Maḥal are very much Ḥadīth, including writing services and teaching services. In this article, only a few well-known scholars have narrated the services of Farangī Maḥal. In addition, care has been taken to mention only the scholars who have a large number of books. The scholars of Farangī Maḥal have written books on the ‘‘Āsma-ur-Rijāl’’, ‘‘Jaraḥ wa T‛adīl’’, and ‘‘Uloom Al Ḥadīth’’, ‘‘types of ḥadīth’’, and ‘‘Fan-e-Ḥadīth’’.
Keywords: Jahãngir; Molānā Quṭub U Dīn Shaeed Sahalvī; Molana Abdul Ḥai Farangī Maḥalī; Ulama-e-Farangī Maḥal